The effects of apomorphine on paracetamol-induced hepatotoxicity in rats - Sehitoglu, Muserref Hilal; Yayla, Muhammet; Kiraz, Asli; Oztopuz, Rahime Ozlem; Bayir, Yasin; Karaca, Turan; Khalid, Sumbul; Akpinar, Erol (Cellular and Molecular Biology, 2017)
It is becoming progressively more understandable that overdose of paracetamol in both humans and animals causes severe hepatotoxicity. Apomorphine is known as a neuroprotective agent. Due to the protective effect, apomorphine had been tested in experimental studies on different models. Findings obtained through series of expriments suggested that apomorphine may also be useful in liver toxicity. The aim of this study is to investigate the relationship among the hepatoprotective mechanism of apomorphine and to determine the possible role of apomorphine on paracetamol-induced hepatotoxicity in rats. 30 Sprague Dawley rats (adult male) were distributed into 5 groups. Group 1 was the control group and did not receive any medication. Group 2 received only paracetamol 2 g/kg by intragastric gavage to induce hepatotoxicity. Groups 3 and 4 were given apomorphine 1 mg/kg and 2 mg/kg by intraperitoneal injection, respectively. Groups 3 and 4 were given 2g/kg of Paracetamol. In Group 5, rats were treated with 2 mg/kg of apomorphine. Drug-treated rats were given food for the next 24 h until they were sacrified. Moreover, we also performed AST, ALT measurements in serum, MDA and SOD levels in liver tissues and histopathological analysis of the liver in all groups. Apomorphine had positive effects on both liver enzymes, oxidative stress markers and histopathological results in paracetamol-induced hepatotoxicity. Additionally, apomorphine at 2 mg/kg dose was significantly more protective as compared to 1 mg/kg as evidenced by the histopathological examination results. It was thought that apomorphine was found hepatoprotective on paracetamol-induced hepatotoxicity, especially at higher doses such as 2 mg/kg.